Profile of Natural Medicine Registration Document Compliance for Stunting Prevention in 2021–2023 - Rima Dwi Pratiwi; Erna Rahmawati (Badan Pengawas Obat dan Makanan, 2025)
Stunting is one of the indicators of social and economic problems in a country. As part of efforts to prevent stunting, one of the strategies that can be implemented is the use of herbal medicines. This study examines the registration process for herbal medicines aimed at preventing stunting, submitted to the Indonesian Food and Drug Authority (Badan POM) between 2021 and 2023. A total of 900 products have been registered with an increasing annual trend, indicating high interest from businesses in producing and registering these products. Although awareness of the importance of product registration to ensure safety and quality has increased, there are still significant issues related to the incompleteness of the necessary documents. This research showed that, on average, 77% of product submissions were still incomplete, particularly from the UKOT group, which accounted for 90%. This analysis found that aspects of quality and labeling often failed to meet the standards set by Badan POM Regulation No. 25 of 2023. The study suggests that simplifying the registration procedures and more targeted interventions, such as the provision of educational materials and more intensive training, can help address these issues. Additionally, the research recommends further surveys to specifically identify the obstacles faced by businesses, which will assist in the design of more effective policies to support the improvement of quality and speed in the product registration process in the future.